Fostering Entrepreneurial Education and Unravelling the Conundrum of Entrepreneurial Intention: A Conceptual and Empirical Insights - Karl Ponteras Campos (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: A considerable agreement exists about the importance of fostering entrepreneurship education in developing student’s entrepreneurial intention. In particular, this research investigates the effect of entrepreneurship education on entrepreneurial intention of students among State, Universities, and Colleges (SUCs) in Davao Region, Philippines. Design/methodology/approach: In order to address the quandary of this study, a survey questionnaire was administered to 463 enrolled students in business-related courses. Pearson product moment correlation was used to determine the interrelationship of variables. Findings: The results show that entrepreneurial education shows a significant relationship with students’ entrepreneurial intention considering its different measures and variables. Research limitations/implications: Hence, those students enrolled on business related courses who have sufficient knowledge and comprehension about the study were taken into consideration. On the other hand, enrolled students in non-business-related degree were excluded as they cannot truly assess the entrepreneurial intention of students because of the nature of their field of study and scope set by the researcher. Practical implications: Indeed, it’s a call for educational institutions and curriculum developers to foster and promote entrepreneurship in the learning institutions for many successful entrepreneurs are honed and harnessed in the university. From a practical point of view, entrepreneurial education plays a significant role in motivating students to venture into business as an option to employment nor as a career. Originality/value: The researcher certifies that this research is original to the best of his knowledge. Paper type: Research Paper